MUTU PELAYANAN PUSKESMAS RAMAH ANAK - Sarwono, Bambang (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2019)
The city of Magelang is one of the implementers of a child-friendly service quality program. Children have the right to obtain satisfactory health services, one of which is the service of childfriendly health centers. Children who come to the Puskesmas are expected to get comfort during the examination process. Research conducted at the Puskesma of Magelang City showed that the perceived quality of child-friendly Puskesmas services provided by health workers was good, but the assessment to the satisfaction of the quality of children's services was still lacking especially in terms of infrastructure such as the absence of food and beverage facilities for children. mother and child while breastfeeding such as the ASI corner room, a playground in the waiting room and playground equipment for children during health checks. This facility is very useful for making children not anxious or afraid when examined so as to eliminate the trauma of children during health checks. In the absence of trauma, it is hoped that children will be easily invited to seek treatment at the Puskesmas when they are sick, so that they can be treated quickly. Management organization policy is needed to fulfill infrastructure facilities for children. The better quality ofservice provided will further increase customer satisfaction.